Somoza and Roosevelt : good neighbour diplomacy in Nicaragua, 1933-1945 - Crawley, Andrew (Oxford historical monographs., 2007)
Crawley examines US non-intervention in another country's affairs, and how it could be detrimental both to the United States and to the country in question - in this case, Nicaragua. He analyses the relations between the United States and Nicaragua during the Depression and the Second World War.